ANALYSIS OF SEMIOTICS IN VIDEO CLIPS "MAN UPON THE HILL" STARS AND RABBITS - ANGGY RUSIDI, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The Man Upon The Hill Video Clip is full of unique visual communication graphic content such as  the appearance of some symbols in this clip that affect the number of viewers, with a non-linear plot. This research intention is to identify the symbols contained in the video clip and find out the  meaning of the visual in the video clip o  Man upon the Hill.This research using a semiotical method proposed by Roland Barthes, sign as meaning with  denotation and connotation level, with connotation level two. Using the qualitative methods in  collecting the data, the data was collected by dividing the video clips based on the scene and  identifying symbols and meanings contained in the video clips that are supported by interview data.The Man Upon the Hill video clip as a whole presents the meaning of human spirituality with nature  presented in various symbols along with supporting natural elements such as; water, fire, and earth  (land), which are presented through this visual video clip.Keywords: Video Clips, Symbols, Human Spirituality